Pricing Urban Water Evaluation of Economics in the Water Sector of Hyderabad and Varanasi (India) - Echternacht, Laura (SpringerBriefs in Water Science and Technology, 2014)
High population growth, informal settlements, and organizational and financial mismanagement represent major challenges for the water supply in many cities in developing countries. This book contributes to solving those problems by identifying systematic shortcomings and proposing solutions to improve the financial conditions in two representative cities: Hyderabad and Varanasi. Serious improvements are necessary for the further development of the water supply and sanitation networks in these areas.   Pricing Urban Water offers a theoretical introduction to economics of the water sector, including the theory of water pricing and tariff systems, combined with detailed analyses of the water supply and sanitation infrastructure as well as of the municipal suppliers of Hyderabad and Varanasi. Introducing a method for estimating future water production costs in both cities serves as the basis for a tariff revision, which is put forward as one solution to improve the poor financial conditions both suppliers are in. Besides the revision of the tariff systems, some considerations on how to supply and charge urban poor and on the inclusion of private borewells in the tariffs are part of the discussion. Changes in both the organizational structure of the service providers and in the current delivery and use of the services are presented as further solutions to the problems in this sector.